Analysis of Influence Factors of Pore Water Pressure Change in Frozen Soil - Kun Zhang; Lianhai Zhang (Advances in Materials Science and Engineering)
In this article, changes of pore water pressures (PWP) in silty clay subjected to freezing and thawing were measured under an open-system condition. A total of five soil samples were tested, with water contents of 10.70%, 18.28%, 23.98%, 31.00%, and 37.65%, respectively. Each experienced a first-step freezing stage, a thawing stage, and a second-step freezing stage. The results showed that changes in PWP depended on the water content, soil type, salinity, ice content, air, pressure, temperature, and others. The PWP minimum with initial water content has a “w-shaped double-valley” characteristic, which described two PWP minima existing in two optimum water contents as initial water content increased. An influence-factor analysis of PWP was proposed and gave a reasonable interpretation on the “w-shaped double-valley” characteristic of PWP. In addition, the tensiometer method to measure PWP in frozen soil was further discussed with regard to its advantages and disadvantages.